Impact Of Training And Development On Employee Loyalty: The Case Study Of Beton 6 Corporation - Vi, Nguyen Thuy; Vi, Tran Thi Tuong; Quang, Ho Nhut (Archives of Business Research, 2018)
Training and development is a fundamental element to meet the goals, strategies of the organization. The quality of human resources does not currently meet the demands of the enterprises. One of the biggest drawbacks in employees is the lack of their own thinking ability, creativity, and initiative in their work. The research focuses on the question of how Training and Development impact on Employee Loyalty and what the factors affecting employee loyalty are. The purpose of this research is to identify and evaluate the impact of Training and Development on Employee Loyalty - The case of Beton 6 Corporation, which examine how Training and Development affect Employee Loyalty through Technique Skills, Functional Skills, Supervisor Support, and Employee Performance. The research uses descriptive statistics and quantitative method (the survey was taken in 2017 via questionnaires with sample size n = 512 employees aging from 25 to more than 45 with many types of work). The conceptual model is based on the model by Muhammad & Aiman (2015) to measure the impact of Training and Development on Employee Loyalty. After analyzing the data using SPSS and AMOS software, the research results show that Training and Development indirectly affect Employee Loyalty and the factor Employee Performance has the highest levelof direct influence on Employee Loyalty. Although there are some limitations to this study, such as samples, questionnaires and data collection, this research hopes to contribute meaning to future research on employee loyalty in the field of construction and concrete production.